2022
DOI: 10.1002/em.22506
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA RNF10 inhibits tumorigenicity by targeting miR‐942‐5p/GOLIM4 axis in breast cancer

Abstract: We aimed to explore the action of a circRNA produced by ring finger protein 10 (circ_RNF10; hsa_circ_0028899) in the malignant behaviors of breast cancer (BC) and to explore its potential action‐of‐mechanism. The levels of circ_RNF10, miR‐942‐5p and Golgi integral membrane protein 4 (GOLIM4) were measured through quantitative real‐time polymerase chain reaction, western blot, or immunohistochemistry, and the competing endogenous RNA (ceRNA) relationship among them was verified by dual‐luciferase reporter assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…As for the biological function of circRNF10 in BC, we discovered that circRNF10 inhibited BC proliferation and progression. These findings were consistent with previous studies, which showed that circRNF10 inhibited tumorigenicity by sponging miR-934 and miR-942-5p in BC [ 15 , 16 ]. Considering the inhibitory effect of circRNF10 on BC, it raised the possibility that circRNF10 might become an agent for BC treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As for the biological function of circRNF10 in BC, we discovered that circRNF10 inhibited BC proliferation and progression. These findings were consistent with previous studies, which showed that circRNF10 inhibited tumorigenicity by sponging miR-934 and miR-942-5p in BC [ 15 , 16 ]. Considering the inhibitory effect of circRNF10 on BC, it raised the possibility that circRNF10 might become an agent for BC treatment.…”
Section: Discussionsupporting
confidence: 93%
“…As for the cytoplasmic circRNAs, they mostly acted as a sponge of miRNAs [ 34 ] and decoys of proteins [ 35 ]. Previous studies have explored the role of circRNF10 as an miRNA sponge [ 15 , 16 ]. Differing from these studies, we focused on the potential of circRNF10 in binding proteins and discovered a novel role in which it could bind to DHX15 in BC by interacting with the RecA2 domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation